Executive function in high functioning individuals with age-associated memory impairment or Alzheimer's disease. - Vasudev, Linda. (University of Ottawa (Canada), 2000)
The purpose of the study was to explore the possibility that age associated memory impairment (AAMI) may form part of a prodromal stage of Alzheimers Disease (AD) through evidence of dysfunction beyond memory, involving also executive function. A sample of subjects meeting AAMI criteria least likely to show executive dysfunction was selected for study by specifying that all participants belonged to a "high functioning" group. As such, all subjects had completed 16 or more years of education. A total of 88 subjects were recruited for the study: 22 young control subjects (YC), 22 older control subjects (OC), 22 subjects with AAMI as specified by the NIMH Work Group criteria, and 22 subjects with mild to moderate probable AD according to NINCDS-ADRDA criteria. The young subjects were recruited to provide appropriate education-based norms for tests of recent memory required for AAMI inclusion criteria. Six executive function tests were used including: Controlled Oral Word Association (COWA), Colour Trails Test (CTT), Similarities subtest of the WAIS-R, Stroop Colour Word Test, Tower of Toronto (TOT), and the Wisconsin Card Sorting Test (WCST). Results indicated the AD group performed significantly worse than both the AAMI and OC groups on all six tests, providing evidence of test sensitivity to executive dysfunction in AD, and confirming the presence of executive function deficits early in the disease course. AAMI and OC groups only differed on the COWA and the TOT. However, when the AAMI subjects were compared to the OC subjects, independent of the AD group, significant differences were found on the COWA, TOT, two indices of the WCST, and CT1. Profile analysis indicated the two groups were not statistically parallel, though examination of the pattern of executive function performance of the AAMI group revealed some similarities to that of the AD sample. It was concluded that AAMI is not merely a mild memory disorder, but that it fulfills to some degree, the criteria of probable AD, and as such, may be a prodromal stage in the development of AD. Current results are deemed particularly important in light of the most recent findings indicating that it is the earliest intervention with anti-dementia compounds which provides the most therapeutic benefit. Thus, the identification of individuals at the prodromal stage of dementia is imperative.
Keywords: Biology, Neuroscience.